2021
DOI: 10.1088/1742-6596/1844/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

A Stunting Prevention Application “Nutrimo” (Nutrition Monitoring)

Abstract: A total of 11 % of children under the age of five years (toddlers) in Tangerang City experienced stunting. Stunting reflects chronic malnutrition during the most critical period of growth and development in early life, the first 1000 days of life. Monitoring the nutritional status is able to prevent stunting especially through Kartu Menuju Sehat (KMS) at an integrated service post (posyandu). Most of the data in KMS is recorded manually, so the risk of data loss or damage is very high. Therefore, mobile applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As a result, stunting management is not optimal. Currently, online, android, and offline versions of information technology-based nutritional surveillance have been developed as a source of real-time data and information 8,23,33 . However, it has not been fully in national scope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, stunting management is not optimal. Currently, online, android, and offline versions of information technology-based nutritional surveillance have been developed as a source of real-time data and information 8,23,33 . However, it has not been fully in national scope.…”
Section: Discussionmentioning
confidence: 99%
“…Stunting prevention using Android applications can be used by health cadres and health professionals at the village, regional, and central levels to collect real-time data and furthermore can be used as a basis for providing counseling regarding problems faced by mothers and babies who are at risk of stunting 8,[23][24][25] . It is suggested that every policy should have an accurate database so that the programs provided can be more effective, efficient and right on target.…”
Section: Introductionmentioning
confidence: 99%